The Proposition of an EI Equation of Square and L–Shaped Slender Reinforced Concrete Columns under Combined Loading - Hamzaoui, L.; Bouzid, T. (Engineering, Technology & Applied Science Research, 2021)
The stability and strength of slender Reinforced Concrete (RC) columns depend directly on the flexural stiffness EI, which is a major parameter in strain calculations including those with bending and axial load. Due to the non-linearity of the stress-strain curve of concrete, the effective bending stiffness EI always remains variable. Numerical simulations were performed for square and L-shaped reinforced concrete sections of slender columns subjected to an eccentric axial force to estimate the variation of El resulting from the actual behavior of the column, based on the moment-curvature relationship. Seventy thousand (70000) hypothetical slender columns, each with a different combination of variables, were used to investigate the main variables that affect the EI of RC slender columns. Using linear regression analysis, a new simple and linear expression of EI was developed. Slenderness, axial load level, and concrete strength have been identified as the most important factors affecting effective stiffness. Finally, the comparison between the results of the new equation and the methods proposed by ACI-318 and Euro Code-2 was carried out in connection with the experimental results of the literature. A good agreement of the results was found.